Environmental Social Work: Mitigating the Impact of Environmental Crises on Older People Living in Disaster Prone Areas in Nepal - Khanal, Diwakar; Dangal, Megh Raj (Bodhi: An Interdisciplinary Journal, 2022)
Older people themselves have a key role in adapting to the impact of environmental disasters rather than being a vulnerable group. They have useful knowledge, skills, and experience which can help them to be resilient in times of disaster preparedness and responses. In such context, this paper highlights the concern for the well-being of older people in Nepal against environmental threats. It further draws attention to how inequalities shape the impact of environmental crises showing stronger connections between the concept of eco-social work and empirical discussions from several kinds of literature. The article provides some recommendations for social work practice in the context of Nepal about environmental crises on older people.